AN INVESTIGATION ON THE NONLINEAR BEHAVIOR OF UNREINFORCED MASONRY WALLS - Jafarov, Oktay; Koksal, H. Orhun; Doran, Bilge; Karakoc, Cengiz (YILDIZ TECHNICAL UNIV, 2012)
Recently, numerous studies on the modeling technique for masonry structures and their structural components have been carried out, such as masonry shear walls existing in the literature. This paper is focused on nonlinear finite element modeling of masonry walls at a micro-level. For this purpose, Drucker-Prager yield criterion is employed in the elasto-plastic analyses of walls deriving the material parameters from the compressive strength of both brick and mortar. The performance of the proposed approach is verified by simulating a series of experiments reported in the literature.
Keywords: Elastoplastic analysis; Drucker-Prager yield criterion; unreinforced masonry walls; Engineering